Testing the Social Investment Principle around childbirth: Little evidence for personality maturation before and after becoming a parent - Eva Asselmann; Jule Specht (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
In line with the Social Investment Principle, becoming a parent should lead to more mature behavior and an increase in conscientiousness, agreeableness, and emotional stability. However, previous research provided mixed results that do not support this idea. Here, we used data from a nationally representative household panel study from Germany (N = 19,875) to examine whether becoming a parent relates to personality maturation. Whether a child was born was assessed yearly and the Big Five personality traits were measured in four waves from 2005 to 2017. We used multilevel analyses to investigate whether personality differs between individuals who will or will not become parents, whether personality differs before and after becoming a parent, and whether these effects vary by gender, age, and living status. In sum, our findings revealed that less open and more extraverted individuals were more likely to start a family, and openness and extraversion both decreased after the transition to parenthood. Some other effects varied by gender, age, and living status. Taken together, our findings suggest that the Big Five personality traits differ before and across the transition to parenthood and that these differences especially apply to openness and extraversion.
Keywords: 330; personality development; Big Five; parenthood; life event; longitudinal